ASPEK YURIDIS TERHADAP PERBUATAN PIDANA YANG DIKLASIFIKASIKAN SEBAGAI PERBUATAN YANG DITERUSKAN DI PERUSAHAAN (PENERAPAN PASAL 374 KUHP JO PASAL 64 KUHP) - Fauzi, Alfiyan (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
AbstractThe application of Article 374 of the Criminal Code jo article 64 paragraph (1) of the Criminal Code by the Panel of Judges in the criminal case No.15/Pid.B/ 2015/PN.Smda is correct, but regarding the duration of the sentence handed down by the Panel of Judges regardless of the things incriminating and relieving the punishment imposed on perpetrators of criminal acts of embezzlement of property of the company conducted in a row. In relation to the criminal case where the defendant was sentenced for 5 (five) months, the author believes that the sentence is very light. In relation to the problem of classification of criminal act of embezzlement as regulated and threatened Article 374 of the Criminal Code jo article 64 paragraph (1) of the Criminal Code is a criminal act of embezzlement with a weighting. The legal consequences of the perpetrators of criminal act of embezzlement with the objections as regulated in Article 374 of the Criminal Code shall be imprisonment for a maximum of 5 (five) years. Whereas in the decision of the criminal case No.15/Pid.B/2015/PN.Smda as described above, against the perpetrator of criminal act of embezzlement of goods owned by the company which is done consecutively included in the classification of criminal act with the imposition of imprisonment for 5 (five) months. Since the act is included in the classification of criminal act of embezzlement with a denunciation, it should be terminated with considerable punishment.